2021
DOI: 10.1016/j.berh.2020.101657
|View full text |Cite
|
Sign up to set email alerts
|

Novel coronavirus disease-2019 (COVID-19) in people with rheumatic disease: Epidemiology and outcomes

Abstract: There is concern that people with rheumatic disease, often treated with immunosuppressive or immunomodulatory medication, may be at increased risk of poor outcomes of novel coronavirus disease-2019 (COVID-19). However, hyperinflammation is a major cause of morbidity and mortality in COVID-19 and treatment with glucocorticoids has been shown to improve outcomes in patients with severe COVID-19. Therefore, uncertainty exists about continuing or withholding immune therapies with risk of infection of severe acute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 53 publications
1
27
0
2
Order By: Relevance
“…Whether patients with RD, especially those receiving DMARDs, are at an increased risk for severe COVID-19 infection remains unclear [14]. So far, rheumatic diseases are not listed among the comorbidities that carry increased risk for severe COVID-19 [15].…”
Section: Discussionmentioning
confidence: 99%
“…Whether patients with RD, especially those receiving DMARDs, are at an increased risk for severe COVID-19 infection remains unclear [14]. So far, rheumatic diseases are not listed among the comorbidities that carry increased risk for severe COVID-19 [15].…”
Section: Discussionmentioning
confidence: 99%
“…However, current limitations should be taken into account in the interpretation of studies and case reports. In particular selection bias and confounding are important to consider [39]. We want to acknowledge that our recommendations are based on the aforementioned and currently available data and evidence, and that it has to be updated based on ongoing data.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, other studies and case reports of patients with rheumatic diseases showed no direct and significant relation between GC use and the risk of a severe course of disease [36][37][38]. In general, the outcome for patients with rheumatic diseases does not seem to differ from that of the general population when demographic factors and comorbidities are taken into account [39]. However, since medication use and outcomes are most likely associated [31], GC administration per se already has many unfavorable The risk for a severe course of disease or death due to COVID-19 was as well analyzed in studies of patients with chronic inflammatory diseases (Table 1).…”
Section: Risk In Exogenous Glucocorticoid Excessmentioning
confidence: 92%
“…1). У пациентов с ИВРЗ пожилой возраст, неконтролируемое воспаление и иммуносупрессия, исходно необратимое повреждение внутренних органов, коморбидная патология (встречается чаще, чем в популяции) [76,77], генетические и другие факторы потенциально могут приводить к увеличению восприимчивости к SARS-CoV-2 (и сопутствующим вирусным и бактериальным инфекциям), нарастанию риска тяжелого течения COVID-19, снижению эффективности терапии как ИВРЗ, так и COVID-19 [78][79][80][81][82][83][84][85][86]. Кроме того, инфекция SARS-CoV-2 потенциально способна индуцировать обострение иммуновоспалительного процесса [69] или развитие «новой» аутоиммунной патологии.…”
unclassified